Complex cold crystallisation peaks in PET/PS blends. (February 2015) - Wellen, Renate M.R.; Canedo, Eduardo L.
Abstract: This work describes the investigation of complex peaks observed during the cold crystallisation of polyethylene terephthalate (PET) blended with polystyrene (PS). Blends of PET with 1% to 15% PS content were compounded in a laboratory internal mixer and quenched from the melt to produce substantially amorphous samples. The cold crystallisation behaviour was studied using differential scanning calorimetry (DSC) conducted at 10 °C/min. The complex peaks of the PET/PS blends were resolved as the sum of two simple peaks, and the component peak characteristics were determined. While the total crystallinity was found to be independent of the PS content, the areas under the component peaks depend on the amorphous component content. A simple model based on partial dissolution and micro-segregation of PS is proposed to qualitatively explain the presence of the double cold crystallisation peaks.